The use of basalt scoria as a geopolymer cement to increase soil bearing capacity - Saparudin, Saparudin; Alisjahbana, Sofia W; Rajiman, Rajiman; Sadad, Ilyas; Amin, Muhammad; Hendronursito, Yusup (Brawijaya University, 2023)
One method that can be used to improve soil properties is the addition of geopolymer cement to the soil to become more stable. This study aimed to determine the effect of geopolymer cement on soil stability. The raw materials for geopolymer cement include clay and basalt rock, with variations in the composition of 0%, 20%, 30%, 40%, and 50%. The levels of temperature variance used were 40 oC, 60 oC, and 80 oC, with variations in 4 and 6 hours. Characterization includes X-ray fluorescence (XRF), X-ray diffraction (XRD), and scanning electron microscope (SEM) tests of raw materials and products. The highest compressive strength was obtained on a mixture of 40% basalt, 200 mesh, and a heating temperature of 80 Â°C for 6 hours, 56.32 MPa. The California Bearing Ratio (CBR) test showed a significant increase in the heat treatment geopolymer products. The CBR value on y1 during the 10x collision was 16.67%; in the 30x crash, it increased to 63.33%, while in the 65x collision, it increased to 78.33%. Whereas in the Y2 measurement, at 10x collisions, it was 21.11%; at 30x collisions, the CBR value increased to 82.22%; and at 65x collisions, the CBR value increased to 100.00%.